2010
DOI: 10.1007/bf03216932
|View full text |Cite
|
Sign up to set email alerts
|

Chinese students’ perception of out-of-class groupwork in Australia

Abstract: Despite increasing number of mainland Chinese students studying in western tertiary settings, there is limited information available on their learning experiences and responses to popular educational practices in these contexts. There is an assumption in the literature that Chinese students respond well to the collaborative demands of groupwork due to the collectivist nature of their culture, however there are few reports to substantiate this claim. This paper reports on mainland Chinese students' perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…They stated that group work helped students remember information better than the students who worked individually. Many other studies supported this idea (Gomleksize, 2007;Tuan & Neomy, 2007;Wichadee, 2007;Li et al, 2010;Nihalani et al, 2010;Li & Vandermensbrugghe, 2011 among others).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…They stated that group work helped students remember information better than the students who worked individually. Many other studies supported this idea (Gomleksize, 2007;Tuan & Neomy, 2007;Wichadee, 2007;Li et al, 2010;Nihalani et al, 2010;Li & Vandermensbrugghe, 2011 among others).…”
Section: Discussionmentioning
confidence: 85%
“…It has shown that group work helps students learn and remember knowledge better than individualistic learning (Cockrell et al, 2000;Johnson et al, 2000). Overall, research demonstrates that group work results in better achievement and more effective relationships among students (Gomleksize, 2007;Tuan & Neomy, 2007;Wichadee, 2007;Li et al, 2010;Nihalani et al, 2010;…”
Section: General Advantagesmentioning
confidence: 99%
See 3 more Smart Citations